An Overview of Risk Management Planning - Martie Gillen; Beatrice Pierre (EDIS)
As risks evolve and diversify, approaches to conducting business require a targeted focus on risk management, particularly in agriculture. This new 3-page document explores risk in agriculture, the need to understand risk, formation of strategies to manage risk, and government programs that exist to help growers and producers manage risk. Written by Martie Gillen and Beatrice Pierre, and published by the UF/IFAS Department of Family, Youth and Community Sciences, May 2019. http://edis.ifas.ufl.edu/fy1482